Pengaruh Lama Fermentasi pada Kualitas Pupuk Kandang Kambing - Rino Anggi Wijaksono; Rijadi Subiantoro; Bambang Utoyo (Politeknik Negeri Lampung, 2016)
Goat is one of animal by the village people in Indonesia is one of the goat farm animals are much in demand by the people of the village. Adult goats capable produce solid fecal waste as much as 0.5 kg per day, in the long term this will be a problem if not handled properly. Goat manure can be used as fertilizer. In the manufacture of manure requires serious attention because during the fermentation progresses, there is variety of transformation processes in fertilizers. The purpose of this study was to observe the effect of fermentation on the quality of goat manure. This study was conducted in State Polytechnic of Lampung in October 2014 until February 2015. The experimental design used was a randomized block design (RBD) consisted of six treatment fermentation period: 2, 4, 6, 8, 10, and 12 weeks with three replications.length of fermentation showed the presence of a marked influence on C/N ratio. The value of C/N ratio has decreased accordance with the length of fermentation time, indicated in the treatment of older fermentation 8, 10, and 12 which have a value of C/N ratio is getting smaller 15, 12, and 10.The nutrient content of N and P unless the element K not significantly different, but all three have increased. Based on research that has been done, it can be concluded that the length of fermentation effect on the value of C/N ratio, the content of N and P, but has no effect on the value of the content of K manure goats and best quality was obtained in treatment fermentation period of 10 weeks with a value of C/N ratio 12 and N content of 1.16%, P: 1.01%, and K: 1.27%.Keywords: fermentation duration, goat manure, organic fertilizerPermalink: http://jurnal.polinela.ac.id/index.php/AIP/article/view/50